Citra Tematik Destinasi Kota: Studi Komunikasi Wisata Edukasi DIKBS, Budaya Dipasar Oro-Oro Dowo, Dan Alam Disarah Klopo - M. Arfiansyah; Fina Anisa Setyowati; Tri Ayu Larasati; Mohammad Insan Romadhan (CV. ITTC INDONESIA, 2025)
This study examines the thematic image formation of three flagship urban tourism destinations in East Java: Surabaya Zoo (educational tourism), Oro-Oro Dowo Market in Malang (cultural tourism), and Sarah Klopo in Mojokerto (nature-based tourism). Using a qualitative case study method with a thematic approach, the research explores three key dimensions of destination image: cognitive, unique, and affective. Data were collected through observation, in-depth interviews, and content analysis of promotional media and related literature. The findings reveal that all three destinations successfully build strong thematic images through adaptive communication strategies, experiential narratives, and emotional engagement with visitors. Surabaya Zoo stands out as a center for education and conservation, Oro-Oro Dowo Market combines cultural heritage with modern amenities, and Sarah Klopo offers an eco-tourism experience enriched with environmental education and historical values. The study recommends strengthening promotional innovation, improving facilities, and preserving local values to enhance the competitiveness of thematic urban destinations in today’s tourism landscape.